Interspecies NASH disease activity whole-genome profiling identifies a fibrogenic role of PPARα-regulated dermatopontin - Philippe Lefebvre; Fanny Lalloyer; Eric Baugé; Michal Pawlak; Céline Gheeraert; Hélène Dehondt; Jonathan Vanhoutte; Eloise Woitrain; Nathalie Hennuyer; Claire Mazuy; Marie Bobowski-Gérard; Francesco Paolo Zummo; et al. (JCI Insight, 2017)
Nonalcoholic fatty liver disease prevalence is soaring with the obesity pandemic, but the pathogenic mechanisms leading to the progression toward active nonalcoholic steatohepatitis (NASH) and fibrosis, major causes of liver-related death, are poorly defined. To identify key components during the progression toward NASH and fibrosis, we investigated the liver transcriptome in a human cohort of NASH patients. The transition from histologically proven fatty liver to NASH and fibrosis was characterized by gene expression patterns that successively reflected altered functions in metabolism, inflammation, and epithelial-mesenchymal transition. A meta-analysis combining our and public human transcriptomic datasets with murine models of NASH and fibrosis defined a molecular signature characterizing NASH and fibrosis and evidencing abnormal inflammation and extracellular matrix (ECM) homeostasis. Dermatopontin expression was found increased in fibrosis, and reversal of fibrosis after gastric bypass correlated with decreased dermatopontin expression. Functional studies in mice identified an active role for dermatopontin in collagen deposition and fibrosis. PPARα activation lowered dermatopontin expression through a transrepressive mechanism affecting the Klf6/TGFβ1 pathway. Liver fibrotic histological damages are thus characterized by the deregulated expression of a restricted set of inflammation- and ECM-related genes. Among them, dermatopontin may be a valuable target to reverse the hepatic fibrotic process.